2019
DOI: 10.1101/752535
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Moderate amounts of epistasis are not evolutionarily stable in small populations

Abstract: AbstractHigh mutation rates select for the evolution of mutational robustness where populations inhabit flat fitness peaks with little epistasis, protecting them from lethal mutagenesis. Recent evidence suggests that a different effect protects small populations from extinction via the accumulation of deleterious mutations. In drift robustness, populations tend to occupy peaks with steep flanks and positive epistasis between mutations. However, it is not known what happens when… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…At the same time, the altered selection coefficients of all mutations change the eco-evolutionary dynamics such that Muller’s ratchet becomes less severe and the population can cope with the increased mutation pressure. Sydykova et al (53) have recently explored a related model of tunable epistasis, in which they found that epistasis can evolve in different directions under high mutation rates. Whether weakening the effects of deleterious mutations can lead to survival has been modeled in the research area of quasi-species theory, where a so-called “error threshold” determines the condition in which mutation overwhelms selection (54, 55, e.g., for finite populations,).…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, the altered selection coefficients of all mutations change the eco-evolutionary dynamics such that Muller’s ratchet becomes less severe and the population can cope with the increased mutation pressure. Sydykova et al (53) have recently explored a related model of tunable epistasis, in which they found that epistasis can evolve in different directions under high mutation rates. Whether weakening the effects of deleterious mutations can lead to survival has been modeled in the research area of quasi-species theory, where a so-called “error threshold” determines the condition in which mutation overwhelms selection (54, 55, e.g., for finite populations,).…”
Section: Discussionmentioning
confidence: 99%